IMPLEMENTATION OF FINANCIAL RISK MANAGEMENT IN IMPROVING THE PROFITABILITY PERFORMANCE OF THE ISLAMIC BANKING SECTOR - Nanda Ayu Frastika; Yanti Susanti; Nisma Natasha Arla; Wilyan Arta Almajid (International Journal of Economics, Education, Law and Social Sciences (IJEELSC), 2025)
The transformation of the global economic paradigm towards a sustainable financial system puts Islamic banking in a strategic position but faces the complexity of challenges in optimizing profitability. This research aims to analyze the implementation of financial risk management in improving the profitability performance of the Indonesian Islamic banking sector. The research method uses an explanatory quantitative approach with data analysis of a panel of 15 Islamic banks for the 2019-2023 period. The results showed an average NPF of 3.2%, FDR of 89.4%, and CAR of 22.5% with variability indicating risk complexity. The effectiveness of risk management was positively correlated significantly with ROA (r=0.68, p<0.01) and ROE, where large banks achieved an effectiveness score of 78.5% compared to 58.9% of small banks. Digital technology integration shows 67% adoption with a 32% increase in operational efficiency. A one-unit increase in effectiveness score contributed to a 0.034% ROA growth and an ROE of 0.28%. The study concludes that the implementation of optimal risk management has a significant impact on profitability with a lag effect of 6-9 months, confirming the strategic imperative for sustainable investment in risk management infrastructure.